Implementation of Pangkalpinang City Regional Regulation Number 7 Year 2015 About Handling of Homeless People, Beggars, and Street Children - Diana Susmantri Yuliyanti (Inovbook Publications, 2021)
Implementation is an implementation or an application where there is already a regional regulation in the City of Pangkalpinang Number 7 of 2015 concerning Handling Homeless, Beggars, and Street Children, The problem that occurs in Pangkalpinang City is that there are still homeless people, beggars, and street children who are in public places, highways, and red lights. themselves on the streets. The purpose of this study is to determine whether or not the Pangkalpinang City Regional Regulation Number 7 of 2015 concerning Handling Homeless, Beggars, and Street Children has been implemented and the next goal is to find out what are the supporting and inhibiting factors of the Pangkalpinang City Regional Regulation Number 7 Hold 2015 . The theory used in this study is the theory of Edward III's Policy Implementation which in Edward III's theory has four variables indicating that a policy has been implemented or has not been implemented, the variables are communication, resources, disposition, and bureaucratic structure. The method used in this study is a descriptive qualitative method whose primary source is interviews with 9 informants. The informants were from 1 Pangkalpinang City Social Service agency, 1 Pangkalpinang City Satpol PP agency, 1 agency from the Women's Empowerment Service for Child Protection and Family Planning, 2 community red light intersections seven, 2 red light communities at the Ramayana intersection, 2 red light communities at the intersection of semabung. The results of this study indicate that the Pangkalpinang City Regional Regulation Number 7 of 2015 concerning Handling Homeless, Beggars, and Street Children has been implemented, The supporting factor of this research is the completeness of facilities such as buildings, vehicles and human resources in handling the Pangkalpinang City Regulation Number 7 of 2015, the inhibiting factor is financially, namely funds because the distribution of these funds is for handling Covid-19.